Customer use of online order for food delivery service: the application of UTAUT2 Model - Osei, Francis; Agyemang, Gertrude; Kankam-Kwarteng, Collins; Amofah, Ofosu (Technium Social Sciences Journal, 2021)
Purpose – Online Food Delivery service can be defined as a service offered by a Restaurants or any food services business that allows the customers of such establishments to carry out a variety of Online Food Delivery operations via a mobile device, such as a mobile phone, tablet or personal digital assistant. The purpose of this paper is to examine factors that influence customers to adopt and subsequently use Online Food Delivery services in Ghana using the unified theory of acceptance and use of technology 2 (UTAUT2). Design/methodology/approach – Using a questionnaire survey, the study sampled 200 users of online Food Delivery service app in Ghana as respondents. The primary data collected were analyzed using SmartPLS software. Findings – Findings of the study indicate that performance expectancy, effort expectancy and Perceived control were determinants that positively influenced the purchase intention of consumers. On the other hand, we found that ease of use, facilitating conditions, hedonic motivation, social influence, and price value were not key factors determining the purchase intention of delivery apps. The applicability of the UTAUT2 model was confirmed in the context of the research. Practical implications – online order for food is a new phenomenon in Ghana’s hospitality industry, thus it is imperative to understanding customer adoption behaviour. The outcome will aid any food services business to develop strategies that will sustain the interest of consumers to embrace online Food Delivery services. Originality/value – This paper is among the first-ever known attempts to examine online Food Delivery service adoption in Ghana using the UTAUT2 model.